Analisis Visual Kampanye “Plastic Album Sins” Oleh Kpop4Planet - Fadhilah Nur Raudhah Gandidi; Ganis Resmisari (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2026)
This study analyzes the visual strategies employed in the digital campaign Plastic Album Sins by Kpop4Planet as a critique of plastic-based production and marketing practices in the K-pop physical album industry. The research focuses on visual elements such as color, metaphor, typography, and framing in the campaign materials. A qualitative descriptive method was applied using visual semiotic and framing analysis to examine posters and official social media content published by the campaign. The findings indicate that the campaign consistently frames plastic waste as a structural issue within the industry rather than merely a consequence of individual fan consumption. The dominant use of red as a marker of crisis, metaphors of stacked albums, and the “red flag” symbol in fancall raffles construct a critique of exploitative marketing strategies that encourage excessive consumption. Thus, the campaign visuals function not only as informational media but also as instruments of advocacy that shift moral responsibility from individual consumers to the broader entertainment industry system.